PERCEIVED FATHER INVOLVEMENT AND FLOURISHING AMONG MOTHERS OF CHILDREN WITH NDD - Gloria Wilhelmina Manuhutu; Wahyuni Kristinawati (Bajang Institute, 2026)
There were 13.5 million cases of child developmental disorders recorded in Indonesia in one year. Mothers with children who have developmental disorders face greater challenges in parenting than usual, challenges that can affect the flourishing of mothers. This study aims to determine the relationship between mothers' perceptions of fathers' involvement and mothers' flourishing in caring for children with NDD (Neurodevelopmental Disorder). The research method used is quantitative correlational with purposive sampling technique. Data collection was conducted using two psychological scales, namely the scale of mothers' perceptions of fathers' involvement and flourishing. The results showed no significant relationship between mothers' perceptions of fathers' involvement and mothers' flourishing. These findings imply that mothers' flourishing is not necessarily influenced by their perceptions of fathers' involvement; other factors such as psychosocial, emotional, and psychological conditions also have an influence.